In vivo assessment of genotoxic, antigenotoxic and anticarcinogenic activities of Solanum lycocarpum fruits glycoalkaloidic extract - Munari, Carla Carolina [UNESP]; Oliveira, Pollyanna Francielli de; Leandro, Luis Fernando; Pimenta, Leandra Mara; Ferreira, Natalia Helen; Costa, Juliana de Carvalho da; Bastos, Jairo Kenupp; Tavares, Denise Crispim (Public Library Science, 2014)
The fruits of Solanum lycocarpum, known as wolf-fruit, are used in folk medicine, and because of that we have evaluated both the genotoxic potential of its glycoalkaloidic extract (SL) and its influence on the genotoxicity induced by methyl methanesulfonate. Furthermore, the potential blocking effect of SL intake in the initial stage of colon carcinogenesis in Wistar rats was investigated in a short-term (4-week) bioassay using aberrant crypt foci (ACF) as biomarker. The genotoxic potential was evaluated using the Swiss mice peripheral blood micronucleus test. The animals were treated with different doses of SL (15, 30 and 60 mg/kg b.w.) for 14 days, and the peripheral blood samples were collected at 48 h, 7 days and 14 days after starting the treatment. For antigenotoxicity assessment, MMS was administered on the 14 th day, and after 24 h the harvesting of bone marrow and liver cells was performed, for the micronucleus and comet assays, respectively. In the ACF assay, male Wistar rats were given four subcutaneous injections of the carcinogen 1,2-dimethylhydrazine (DMH, 40 mg/kg b.w.), twice a week, during two weeks to induce ACF. The treatment with SL (15, 30 and 60 mg/kg b.w.) was given for four weeks during and after carcinogen treatment to investigate the potential beneficial effects of SL on DMH-induced ACF. The results demonstrated that SL was not genotoxic in the mouse micronucleus test. In animals treated with SL and MMS, the frequencies of micronucleus and extensions of DNA damage were significantly reduced in comparison with the animals receiving only MMS. Regarding the ACF assay, SL significantly reduced the frequency of ACF induced by DMH.